The pocket instructor, literature : 101 exercises for the college classroom - Fuss, Diana, 1960-; Gleason, William A., 1981- (Book collections on Project MUSE., 2016)
"This is the first comprehensive collection of hands-on, active learning exercises for the college literature classroom, offering ideas and inspiration for new and veteran teachers alike. These 101 surefire lesson plans present creative and interactive activities to get all your students talking and learning, from the first class to final review. Whether you are teaching genres or periods, canonical or noncanonical literature, majors or nonmajors, medieval verse or the graphic novel, this volume provides practical and flexible exercises for creating memorable learning experiences. Help students learn more and retain that knowledge longer by teaching them how to question, debate, annotate, imitate, write, draw, map, stage, or perform. These user-friendly exercises feature clear and concise step-by-step instructions, and each exercise is followed by helpful teaching tips and descriptions of the exercise in action. All encourage collaborative learning and many are adaptable to different class sizes or course levels. A collection of successful approaches for teaching fiction, poetry, and drama and their historical, cultural, and literary contexts, this indispensable book showcases the tried and true alongside the fresh and innovative. 101 creative classroom exercises for teaching literature Exercises contributed by experienced teachers at a wide range of colleges and universities Step-by-step instructions and teaching tips for each exercise Extensive introduction on the benefits of bringing active learning to the literature classroom Cross-references for finding further exercises and to aid course planning Index of literary authors, works, and related topics "--